2016
DOI: 10.1007/s40620-016-0344-z
|View full text |Cite
|
Sign up to set email alerts
|

Incremental peritoneal dialysis: a 10 year single-centre experience

Abstract: IntroductionIncremental dialysis consists in prescribing a dialysis dose aimed towards maintaining total solute clearance (renal + dialysis) near the targets set by guidelines. Incremental peritoneal dialysis (incrPD) is defined as one or two dwell-times per day on CAPD, whereas standard peritoneal dialysis (stPD) consists in three-four dwell-times per day.Patients and methodsSingle-centre cohort study. Enrollement period: January 2002–December 2007; end of follow up (FU): December 2012. Inclusion criteria: in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
67
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(72 citation statements)
references
References 28 publications
(13 reference statements)
4
67
0
1
Order By: Relevance
“…The European Best Practice Guidelines recommend measuring RKF in HD patients using the mean of urea and creatinine clearances and offer suggestions to incorporate this into the HD prescription to allow individual adjustments of dialysis prescription to meet minimum dialysis adequacy targets [8]. However, these guidelines do not recommend an incremental transition from less to more frequent HD over time, while, ironically, according to most peritoneal dialysis (PD) guidelines, PD dose should be adjusted upward parallel to decline in RKF, the preservation of which is a high priority target in PD [4,9].…”
Section: Dear Editormentioning
confidence: 99%
“…The European Best Practice Guidelines recommend measuring RKF in HD patients using the mean of urea and creatinine clearances and offer suggestions to incorporate this into the HD prescription to allow individual adjustments of dialysis prescription to meet minimum dialysis adequacy targets [8]. However, these guidelines do not recommend an incremental transition from less to more frequent HD over time, while, ironically, according to most peritoneal dialysis (PD) guidelines, PD dose should be adjusted upward parallel to decline in RKF, the preservation of which is a high priority target in PD [4,9].…”
Section: Dear Editormentioning
confidence: 99%
“…This approach has been successfully used for peritoneal dialysis patients, not for hemodialysis patients. Additionally, patients on incremental peritoneal dialysis showed a lower decline in RKF, a similar survival rate, and fewer hospitalizations than standard peritoneal dialysis patients [82]. With incremental hemodialysis, dialysis treatment is initiated once or twice weekly – rather than thrice weekly, as in the conventional regimen – if patients have substantial RKF.…”
Section: How To Protect Rkfmentioning
confidence: 99%
“…Third, the glucose exposure of the peritoneum can be minimized from the beginning. Finally, there is evidence showing that incrPD might better conserve RKF [19]. Losing RKF not only leads to a reduction in the quality of life, but it is also an important prognostic factor [20].…”
Section: Incremental Pdmentioning
confidence: 99%
“…Sandrini et al [19] included 105 patients and showed no difference in survival and peritonitis rate over a median time of 17 months when compared to standard PD (stPD; 3–5 exchanges in 24 h). IncrPD was defined by one or 2 dwell times per day.…”
Section: Incremental Pdmentioning
confidence: 99%
See 1 more Smart Citation